Android Based Inventory Stock Design Case Study On The North Jakarta Transportation Service Subject - Rizk, Muhamad; Tjahjono, Budi (Publisher Cv. Inara, 2024)
Study This aim For visualize design general Android- based Inventory Stock system for the North Jakarta Transportation Sub – Department. Referring to Law Number 1 of 2004 concerning state treasury , goods or assets belonging to the state/ region in is all purchased items _ or obtained on burden Budget State/Regional Revenue and Expenditure (APBN/D) or originate from acquisition other valid ones , or items obtained _ based on decision powerful court _ law fixed ( provisions of Article 2 paragraph (2) of the Regulation Government Number 27 of 2014). Analysis the need will used in do development of